The Influence of Halal Awareness on Consumer Purchase Intention of Broiler Chicken Meat in Bogor - Muhamad Arham Amarulhaq; Retnaningsih; Raden Isma Anggraini (Journal of Consumer Sciences, 2026)
Background: Halal awareness is a primary determinant of food consumption behavior, especially for broiler chicken products, as consumer demand for halal certification to increase. Purpose: This study examines the influence of exposure to halal information and religious beliefs on halal awareness and its implications for consumer purchase intent. Method: A quantitative survey design was employed involving 140 respondents (Bogor residents aged over 18 years who had purchased chicken meat in the last three months) selected through purposive sampling. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. Findings: The study demonstrates that exposure to halal information and religious beliefs positively and significantly influence halal awareness. Individuals who receive information from their environment, social media, and religious activities and who possess strong religious beliefs tend to exhibit higher levels of halal awareness. Additionally, greater halal awareness significantly increases consumers’ purchase intentions. Therefore, enhancing halal awareness can effectively strengthen consumers’ intent to purchase. Conclusions: Within this purposive sample of Bogor consumers, halal awareness mediated the relationships between exposure to halal information, religious belief and purchase intention. Because the sample was non probability and localized, caution is needed before generalizing these findings to other regions. Research implication: These findings highlight the importance of halal communication strategies based on credible information and the reinforcement of religious values to enhance the effectiveness of halal product marketing and certification policies.